Screening and Detecting Salmonella in Different Food Matrices in Southern Tunisia Using a Combined Enrichment/Real-Time PCR Method: Correlation with Conventional Culture Method - Siala, Mariam; Barbana, Amina; Smaoui, Salma; Hachicha, Salma; Marouane, Chema; Kammoun, Sana; Gdoura, Radhouane; Messadi-Akrout, Férièle (Frontiers in Microbiology, 2017)
A combined enrichment/ newly developed invA TaqMan® real-time PCR (qPCR) method as a screening assay to detect Salmonella spp. in 500 naturally food matrices is evaluated. DNA template for qPCR was extracted from an overnight pre-enriched sample in buffered peptone water using lysis–guanidine isothiocyanate method. Heterologous internal amplification control (IAC) was incorporated during qPCR assays and co-amplified with the invA gene of the target pathogen. InvA qPCR exhibited 100% specificity when testing 94 Salmonella strains (inclusivity) and 32 non-Salmonella strains (exclusivity). The qPCR showed a consistent detection of two copies of the invA gene/PCR reaction, a good intra- and inter-run reproducibility with a good PCR efficiency (89.6%). QPCR was sensitive and showed Salmonella detection at 8.5 × 100 CFU mL-1 of artificially spiked poultry meat -BWP solution in less than 40 cycles. When analyzing 500 different food matrices and comparing the results with the ISO 6579:2002 conventional culture method, the sensitivity and specificity were 100 and 76.6%, respectively. QPCR showed Salmonella spp. DNA in raw poultry meat 27/45 (60%), milk 31/93 (33.3%), raw red meat 5/13 (38.5%), and fish 11/46 (23.9%) samples. The prevalence of Salmonella spp. in cakes, dairy, cooked meals, charcuterie products using qPCR was 11/14 (26.8%), 5/22 (22.7%), 32/150 (21.3%), and 5/20 (25%), respectively, compared to 0% as demonstrated by culture. S. Anatum was the most common serovar found associated with red meat compared to S. kentucky isolated from fish and poultry meat. In conclusion, our study is the first to use a combined enrichment/invA qPCR method as a screening assay to detect Salmonella DNA in different types of commercialized food in Southern Tunisia. QPCR results indicate that Salmonella contamination is common in milk and in other types of food samples.